Optical resin monomer and preparation method thereof

Through the program heating reaction of raw materials such as dimethyl terephthalate, a tight crosslinking network and nanopore structure are formed, which solves the problem of immature preparation technology of medium and high refractive index lenses and low surface hardness of resins, and achieves high refractive index and resistance Abrasive optical resin monomer improves optical properties and wear resistance.

CN118755243BActive Publication Date: 2024-12-13SHANDONG QINGSHUI CHEM CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411237148.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-13
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

The prior art optical resin monomer preparation technology for high-refractive index lenses is not mature enough, and the surface hardness of the resin material is low and susceptible to wear. Common coating methods increase production processes and costs.

Method used

Optical resin monomers are prepared by dimethyl terephthalate, propylene alcohol, propylene glycol, methyl triethoxysilane, polydimethylsiloxane, nanofunctional fillers, calcium hydroxide and other raw materials, and the process temperature rise method is used. React with stirring to form a tight crosslinking network structure and nano-level pore structure to improve wear resistance and optical properties.

Benefits of technology

The optical resin monomer with high refractive index and wear resistance is achieved. The composite cross-linking of polydimethylsiloxane and methyltriethoxysilane forms a tighter network structure, reducing wear and improving nanofunctional fillers Optical and UV resistance reduce the friction and scratches of the resin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of optical resins, in particular to an optical resin monomer and a preparation method thereof, comprising: adding dimethyl terephthalate, propylene alcohol and catalyst A to a reactor A to react to obtain dipropylene terephthalate; adding dipropylene terephthalate and propylene glycol to a reactor B for reaction; then adding methyl triethoxysilane, polydimethylsiloxane and catalyst B to the reactor B for reaction; then adding nano-functional fillers and dispersants to the reactor B; finally adding dibutyl maleate, diethylene glycol, calcium hydroxide and a permeability enhancer to the reactor B, and cooling to room temperature after stirring to obtain an optical resin monomer product. Polydimethylsiloxane and methyl triethoxysilane are compounded and cross-linked to form a tighter network structure, so that the material is more wear-resistant during friction, and the lubricity and low surface energy of the introduced silicon element also help to reduce wear and improve wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of optical resins, and in particular to an optical resin monomer and a preparation method thereof. Background Art

[0002] Optical resin monomers, through specific polymerization reactions, can form polymer materials with excellent optical and physical properties, and are widely used in the manufacture of various high-precision optical products. In the field of optical lens production, optical resin monomers have become an important choice to replace traditional glass lenses due to their light weight, high light transmittance, good processing performance and adjustable optical properties.

[0003] In the lens industry, a refractive index of 1.60 or above is considered high, a refractive index of 1.56 is considered medium, and a refractive index of less than 1.56 is considered low. At present, the preparation technology of optical resin monomers used to produce low-refractive-index lenses is relatively mature, and there are a variety of materials available on the market. In contrast, the preparation technology of optical resin monomers used to produce medium- and high-refractive-index lenses is still not mature enough and has technical limitations.

[0004] In addition, compared with glass lenses, the molecular structure of resin materials is relatively loose, resulting in lower surface hardness and easy to be scratched and worn by external objects. In order to improve this problem, a common practice is to coat the surface of resin products. Coating can form a protective film to improve the wear resistance of resin products and reduce scratches and wear. However, this method not only increases the production process of resin products, but also increases production costs. Summary of the invention

[0005] In view of the defects mentioned in the background technology, the present invention provides an optical resin monomer with high refractive index and strong wear resistance. The optical resin monomer is prepared from the following raw materials in terms of mass fraction:

[0006] 20-35 parts of dimethyl terephthalate, 50-65 parts of propylene alcohol, 30-40 parts of propylene glycol, 15-25 parts of methyltriethoxysilane, 5-8 parts of diethylene glycol, 3-5 parts of dibutyl maleate, 15-20 parts of nano-functional filler, 8-15 parts of polydimethylsiloxane, 0.5-2 parts of calcium hydroxide, 0.3-1 parts of dispersant and 1-5 parts of permeability enhancer.

[0007] The present invention also discloses a method for preparing an optical resin monomer, comprising the following steps:

[0008] S1. Add 20-35 parts of dimethyl terephthalate, 50-65 parts of propenol and 0.5-1 part of catalyst A to reactor A by weight, start the stirring device, raise the temperature in the reactor to 115-125°C by programmed temperature rising method, and react at the set temperature;

[0009] S2, after the reaction is carried out for 20 to 22 hours, sampling is performed every 0.5 hours to detect the content of dimethyl terephthalate in the reaction system. When the content is less than 0.5%, stirring and heating are stopped to obtain a crude product of dipropylene terephthalate;

[0010] S3, refining the obtained crude dipropylene terephthalate;

[0011] S4, add 30-40 parts of refined dipropylene terephthalate and propylene glycol to the reactor B, start the stirring device, raise the temperature in the reactor to 125-145° C. by a programmed temperature method, and react at the set temperature;

[0012] S5. After the reaction is carried out for 7 to 8 hours, the temperature in the kettle is lowered to 105 to 115°C, 15 to 25 parts of methyltriethoxysilane, 8 to 15 parts of polydimethylsiloxane, and 0.2 to 0.5 parts of catalyst B are added to the reaction system of reactor B and stirred for 1 to 3 hours;

[0013] S6. After the stirring is completed, add 15-20 parts of nano-functional filler and 0.3-1 parts of dispersant into the reactor B, and continue stirring for 0.5-1.5 hours;

[0014] S7. After the stirring is completed, the temperature in the kettle is lowered to 75-85°C, 3-5 parts of dibutyl maleate, 5-8 parts of diethylene glycol, 0.5-2 parts of calcium hydroxide, and 1-5 parts of a permeability enhancer are added to the reaction kettle B, and stirred for 1-2 hours;

[0015] S8. After the stirring is completed, the temperature is lowered to room temperature to obtain an optical resin monomer product.

[0016] Preferably, the refining treatment of the crude dipropylene terephthalate comprises the following steps:

[0017] S31, after stopping stirring and heating, the crude product of dipropylene terephthalate is discharged from the reactor A for filtering;

[0018] S32, the filtered crude dipropylene terephthalate is sent to a distillation tower for distillation to obtain refined dipropylene terephthalate.

[0019] Preferably, the nano-functional filler is compounded by nano-silicon dioxide, nano-titanium dioxide and nano-zinc oxide in a weight ratio of (2-5):(3-4):(2-3).

[0020] Preferably, the catalyst A is a silicotungsto-molybdic acid-doped polyaniline catalyst.

[0021] Preferably, the catalyst B is a platinum catalyst.

[0022] Preferably, the permeability enhancer is polyethylene glycol monoacrylate.

[0023] After adopting the above technical solution, the beneficial effects of the present invention are:

[0024] Polydimethylsiloxane and methyltriethoxysilane are compounded and cross-linked to form a tighter network structure, which reduces the wear points on the surface of the resin product and makes the material more wear-resistant during friction. The lubricity and low surface energy of the introduced silicon element also help reduce wear and improve wear resistance. Polydimethylsiloxane and methyltriethoxysilane are compounded and cross-linked to form a nano-scale pore structure, which achieves the purpose of optical transmittance enhancement by causing light diffraction. DETAILED DESCRIPTION

[0025] The features and exemplary embodiments of various aspects of the present invention will be described in detail below. In order to make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only configured to explain the present invention and are not configured to limit the present invention. For those skilled in the art, the present invention can be implemented without the need for some of these specific details. The following description of the embodiments is only to provide a better understanding of the present invention by illustrating examples of the present invention.

[0026] Example 1

[0027] An optical resin monomer, wherein the weight proportions of the components are:

[0028] 20 parts of dimethyl terephthalate (CAS: 120-61-6), 30 parts of propylene glycol (CAS: 57-55-6), 50 parts of propylene alcohol (CAS: 107-18-6), 5 parts of diethylene glycol (CAS: 111-46-6), 15 parts of methyltriethoxysilane (CAS: 2031-67-6), 8 parts of polydimethylsiloxane (CAS: 9006-65-9), 3 parts of dibutyl maleate (CAS: 105-76-0), 15 parts of nano-functional filler, 0.5 parts of calcium hydroxide, 0.3 parts of dispersant, and 1 part of polyethylene glycol monoacrylate.

[0029] The preparation method of the optical resin monomer of this embodiment is carried out according to the following steps:

[0030] S1. Nitrogen is introduced into the reactor A and the exhaust gas discharge valve is opened to gradually replace the air in the reactor with nitrogen. Under the protection of nitrogen, 20 parts of dimethyl terephthalate, 50 parts of propenol and 0.5 parts of catalyst A are added to the reactor A in proportion, and the stirring device is turned on to mix the materials in the reactor A. The temperature in the reactor A is gradually raised to 115°C by a programmed temperature rise method (the temperature rise program is: room temperature to 80°C, the temperature rise rate is 0.6 to 0.8°C / min, and the temperature rise time is 2 hours; 80 to 115°C, the temperature rise rate is 0.8 to 1°C / min, and the temperature rise time is 0.5 hours). When the temperature reaches 115°C, the reaction is maintained at this temperature. During the reaction, the by-product methanol is evaporated;

[0031] S2, after the reaction is carried out for 20 hours, a small amount of reaction liquid is taken out from the reactor A at a predetermined time interval (every 0.5h), and the content of dimethyl terephthalate in the sample is detected by liquid chromatography. When the test result shows that the content of dimethyl terephthalate in the reaction system is less than 0.5%, it means that the reaction is nearly completed, and stirring and heating are stopped to obtain a crude product of dipropylene terephthalate;

[0032] S3, opening the discharge valve of reactor A, discharging the crude dipropylene terephthalate into a pre-prepared container, filtering the discharged crude product through a filter to remove solid impurities, catalyst A, etc., and delivering the filtered crude dipropylene terephthalate to the feed port of a distillation tower by a delivery pump or pouring, starting the distillation tower, and gradually separating the components in the crude dipropylene terephthalate in the tower according to different boiling points, and distilling off water and by-products to obtain refined dipropylene terephthalate;

[0033] S4, slowly introduce nitrogen into the reactor B and open the exhaust valve to gradually replace the air in the reactor with nitrogen. Under the protection of nitrogen, add the refined dipropylene terephthalate and 30 parts of propylene glycol into the reactor B in proportion, turn on the stirring device to mix the materials in the reactor B, and gradually increase the temperature in the reactor B to 125°C by a programmed temperature rise method (the temperature rise program is: room temperature to 100°C, the temperature rise rate is 0.8 to 1°C / min, and the temperature rise time is 2 hours; 100 to 125°C, the temperature rise rate is 0.8 to 1°C / min, and the temperature rise time is 0.5 hours). When the temperature reaches 125°C, maintain the temperature for reaction to obtain a resin precursor solution;

[0034] S5. After the reaction is carried out for 7 hours, the stirring device is kept running, and the temperature in the kettle is gradually reduced from the set temperature to 105°C and kept stable (the cooling rate is 1-1.5°C / min), and 15 parts of methyltriethoxysilane, 8 parts of polydimethylsiloxane, and 0.2 parts of catalyst B are added to the reaction system of reactor B, and stirred for 1 hour to fully mix all the substances in reactor B;

[0035] S6, keep the stirring device running, after 1 hour, add 15 parts of nano-functional filler and 0.3 parts of dispersant into the reaction kettle B, and continue to stir the reaction system for 0.5 hours to make the nano-functional filler evenly dispersed in the reaction system;

[0036] S7. After the stirring in step S6 is completed, the temperature in the reactor B is gradually reduced from 105°C to 75°C (the cooling rate is 1-1.5°C / min) and kept stable, and then 3 parts of dibutyl maleate, 5 parts of diethylene glycol, 0.5 parts of calcium hydroxide, and 1 part of polyethylene glycol monoacrylate are added to the reaction system in the reactor B. After all the additives are added, the stirring device is kept running, and the reaction system is stirred and mixed for 1 hour to allow all the additives to be evenly dispersed in the reaction system so as to interact with each other;

[0037] S8. After the stirring device has been running for 1 hour, the heating source is turned off to allow the temperature in the kettle to drop steadily and reach room temperature, thereby obtaining an optical resin monomer product.

[0038] In step S1, the catalyst A used is a silicotungstomolybdic acid doped polyaniline catalyst. The silicotungstomolybdic acid doped polyaniline catalyst is composed of two parts: silicotungstomolybdic acid and polyaniline. As a polyoxometalate, silicotungstomolybdic acid has good catalytic performance, while polyaniline provides a good carrier for silicotungstomolybdic acid with its unique doping phenomenon and stability. The ester bond of dimethyl terephthalate is broken under the action of the silicotungstomolybdic acid doped polyaniline catalyst to form corresponding carboxyl and methoxy anions, and the hydroxyl group of allyl alcohol attacks the carboxyl group formed by the broken ester bond to form a new ester bond and methanol. After a series of rearrangement and stabilization processes, diallyl terephthalate and methanol are finally generated.

[0039] In step S5, the catalyst used is a platinum catalyst. In the resin precursor solution, under the action of the platinum catalyst, the ethoxy group in methyltriethoxysilane reacts with the vinyl group in polydimethylsiloxane to form a new silicon-oxygen-silicon bond. As the reaction proceeds, multiple molecular chains are interconnected by the newly formed silicon-oxygen-silicon bonds to form a dense three-dimensional cross-linked network structure. This structure enables the resin product to be better dispersed and resist wear when subjected to external forces, thereby improving wear resistance. The lubricity and low surface energy of the silicon element introduced by the silicon-oxygen-silicon bond also help to reduce wear and improve wear resistance. After cross-linking, due to the close connection between the molecular chains, its hardness is significantly increased. In addition, the silicon-oxygen-silicon bond has a high chemical stability, which enables the resin product to resist the erosion of chemical substances such as acids and alkalis. Polydimethylsiloxane and methyltriethoxysilane are compounded and cross-linked to form a nanometer-level pore structure in the resin precursor solution, and the optical transmittance enhancement purpose is achieved by light diffraction.

[0040] In step S6, the nano-functional filler is compounded by nano-silicon dioxide, nano-titanium dioxide, and nano-zinc oxide in a weight ratio of 2:3:2, and the dispersant is a TDL-ND1 type nano-material special dispersant produced by Nanjing Tianxing New Materials Co., Ltd. Under the action of the dispersant, a stable coating layer is formed on the surface of nano-silicon dioxide, nano-titanium dioxide, and nano-zinc oxide, which reduces the interaction force between the particles, thereby effectively preventing the occurrence of agglomeration.

[0041] The porous characteristics of nano-silicon dioxide can affect the refractive index of the resin and play an optical transmittance enhancement role. Nano-silicon dioxide has extremely high surface activity and can form a good bonding effect with resin molecules, enhance the cohesion of the resin matrix, and thus improve the strength, toughness and ductility of the resin. This enhancement effect makes the optical resin monomer more resistant to external stress during the preparation process and reduces the generation of defects and cracks. The small size effect and high fluidity of nano-silicon dioxide make it evenly distributed in the resin, which can form a denser and smoother surface, thereby reducing friction and wear and improving the wear resistance of the optical resin monomer. Nano-titanium dioxide itself has excellent ultraviolet absorption and reflection properties, and the role of dispersant enables it to be evenly dispersed in the resin, so as to give full play to its anti-ultraviolet properties. Nano-zinc oxide has a broad-spectrum antibacterial property and can inhibit the growth and reproduction of microorganisms such as bacteria and viruses. Adding nano-zinc oxide can give the resin monomer antibacterial function and improve the hygiene and safety of the product. Nano-zinc oxide has a photocatalytic effect under the excitation of ultraviolet light and can decompose harmful gases and organic matter. It provides possibilities for the application of resin materials in biomedical fields such as microscopes.

[0042] In step S7, calcium hydroxide can neutralize the acidic substances in the resin system and adjust the pH value of the resin to an appropriate range. This is of great significance for maintaining the stability of the resin and preventing the corrosion of the resin by the acidic substances. Dibutyl maleate mainly plays the role of plasticization and modification in the optical resin monomer, which helps to improve the flexibility and processing properties of the resin. Diethylene glycol is used as a solvent and a plasticizer to adjust the viscosity and processing properties of the resin. Polyethylene glycol acrylate has good optical transparency, and the ester group and polyethylene glycol segment in its molecular structure help to reduce the scattering and absorption of light inside the resin, thereby improving the light transmittance of the resin. Adding a resin precursor solution as a transmittance enhancer can significantly improve the transparency of the final product, and is also conducive to the regular arrangement of nano-functional filler particles, further increasing the transmittance of light.

[0043] Example 2

[0044] An optical resin monomer, wherein the weight proportions of the components are:

[0045] 25 parts of dimethyl terephthalate, 55 parts of propylene alcohol, 32 parts of propylene glycol, 18 parts of methyltriethoxysilane, 6 parts of diethylene glycol, 3.5 parts of dibutyl maleate, 16 parts of nano-functional filler, 10 parts of polydimethylsiloxane, 1 part of calcium hydroxide, 0.5 parts of TDL-ND1, and 1.5 parts of polyethylene glycol monoacrylate.

[0046] The present invention also discloses a method for preparing an optical resin monomer, comprising the following steps:

[0047] S1. Add 25 parts of dimethyl terephthalate, 55 parts of propylene alcohol and 0.75 parts of silicotungsto-molybdic acid-doped polyaniline catalyst into the reactor A by weight, start the stirring device, raise the temperature in the reactor to 118°C by programmed temperature rising method, and react at the set temperature;

[0048] S2, after the reaction is carried out for 21 hours, sampling is performed every 0.5 hours to detect the content of dimethyl terephthalate in the reaction system. When the content is less than 0.5%, stirring and heating are stopped to obtain a crude product of dipropylene terephthalate;

[0049] S3, refining the obtained crude dipropylene terephthalate;

[0050] S4, add the refined dipropylene terephthalate and 36 parts of propylene glycol into the reactor B, start the stirring device, raise the temperature in the reactor to 128° C. by the programmed temperature method, and react at the set temperature;

[0051] S5, after the reaction was carried out for 7.5 hours, the temperature in the kettle was lowered to 108°C, 18 parts of methyltriethoxysilane, 9 parts of polydimethylsiloxane and 0.25 parts of platinum catalyst were added to the reaction system of reactor B and stirred for 1.5 hours;

[0052] S6. After stirring, add 18 parts of nano-functional fillers (nano-silicon dioxide, nano-titanium dioxide, nano-zinc oxide in a weight ratio of 6:7:5) and 0.5 parts of TDL-ND1 into the reactor B, and continue stirring for 1 hour;

[0053] S7, after the stirring is completed, the temperature in the kettle is lowered to 78.5°C, 4 parts of dibutyl maleate, 6 parts of diethylene glycol, 1.8 parts of calcium hydroxide, and 2.5 parts of polyethylene glycol monoacrylate are added to the reaction kettle B, and stirred for 1.5 hours;

[0054] S8. After the stirring is completed, the temperature is lowered to room temperature to obtain an optical resin monomer product.

[0055] Example 3

[0056] 35 parts of dimethyl terephthalate, 65 parts of propylene alcohol, 40 parts of propylene glycol, 25 parts of methyltriethoxysilane, 8 parts of diethylene glycol, 5 parts of dibutyl maleate, 20 parts of nano-functional filler, 15 parts of polydimethylsiloxane, 2 parts of calcium hydroxide, 11 parts of TDL-ND, and 5 parts of polyethylene glycol monoacrylate.

[0057] The present invention also discloses a method for preparing an optical resin monomer, comprising the following steps:

[0058] S1. Add 35 parts of dimethyl terephthalate, 65 parts of propylene alcohol and 1 part of silicotungsto-molybdic acid-doped polyaniline catalyst into the reactor A by weight, start the stirring device, raise the temperature in the reactor to 125°C by programmed temperature rising method, and react at the set temperature;

[0059] S2, after the reaction is carried out for 22 hours, sampling is performed every 0.5 hours to detect the content of dimethyl terephthalate in the reaction system. When the content is less than 0.5%, stirring and heating are stopped to obtain a crude product of dipropylene terephthalate;

[0060] S3, refining the obtained crude product of dipropylene terephthalate;

[0061] S4, add 40 parts of refined dipropylene terephthalate and propylene glycol to the reactor B, start the stirring device, raise the temperature in the reactor to 145° C. by a programmed temperature method, and react at the set temperature;

[0062] S5. After the reaction is carried out for 8 hours, the temperature in the kettle is lowered to 115°C, and 25 parts of methyltriethoxysilane, 15 parts of polydimethylsiloxane, and 0.5 parts of platinum catalyst B are added to the reaction system of reactor B and stirred for 3 hours;

[0063] S6. After the stirring is completed, 20 parts of nano-functional filler (nano-silicon dioxide, nano-titanium dioxide, and nano-zinc oxide are compounded in a weight ratio of 5:4:3) and 1 part of TDL-ND1 are added to the reactor B, and the stirring is continued for 1.5 hours;

[0064] S7, after the stirring is completed, the temperature in the kettle is lowered to 85°C, 5 parts of dibutyl maleate, 8 parts of diethylene glycol, 2 parts of calcium hydroxide, and 5 parts of polyethylene glycol monoacrylate are added to the reaction kettle B, and stirred for 2 hours;

[0065] S8. After the stirring is completed, the temperature is lowered to room temperature to obtain an optical resin monomer product.

[0066] Example 4

[0067] An optical resin monomer, wherein the weight proportions of the components are:

[0068] 28 parts of dimethyl terephthalate, 58 parts of propylene alcohol, 35 parts of propylene glycol, 20 parts of methyltriethoxysilane, 6.5 parts of diethylene glycol, 4 parts of dibutyl maleate, 18 parts of nano-functional filler, 12 parts of polydimethylsiloxane, 1.2 parts of calcium hydroxide, 0.6 parts of TDL-ND1, and 2 parts of polyethylene glycol monoacrylate.

[0069] The present invention also discloses a method for preparing an optical resin monomer, comprising the following steps:

[0070] S1. Add 28 parts of dimethyl terephthalate, 58 parts of propylene alcohol and 0.85 parts of silicotungsto-molybdic acid-doped polyaniline catalyst into the reactor A by weight, start the stirring device, raise the temperature in the reactor to 120°C by programmed temperature rising method, and react at the set temperature;

[0071] S2, after the reaction is carried out for 20 hours, sampling is performed every 0.5 hours to detect the content of dimethyl terephthalate in the reaction system. When the content is less than 0.5%, stirring and heating are stopped to obtain a crude product of dipropylene terephthalate;

[0072] S3, refining the obtained crude dipropylene terephthalate;

[0073] S4, add the refined dipropylene terephthalate and 35 parts of propylene glycol into the reactor B, start the stirring device, raise the temperature in the reactor to 130° C. by the programmed temperature method, and react at the set temperature;

[0074] S5. After the reaction was carried out for 7.5 hours, the temperature in the kettle was lowered to 105°C, and 20 parts of methyltriethoxysilane, 10 parts of polydimethylsiloxane and 0.35 parts of platinum catalyst were added to the reaction system of reactor B and stirred for 2 hours;

[0075] S6. After stirring, add 18 parts of nano-functional fillers (nano-silicon dioxide, nano-titanium dioxide, nano-zinc oxide in a weight ratio of 6:7:5) and 0.5 parts of TDL-ND1 into the reactor B, and continue stirring for 1 hour;

[0076] S7, after the stirring is completed, the temperature in the kettle is lowered to 78.5°C, 4.5 parts of dibutyl maleate, 5.8 parts of diethylene glycol, 1.5 parts of calcium hydroxide, and 3 parts of polyethylene glycol monoacrylate are added to the reaction kettle B, and stirred for 1.5 hours;

[0077] S8. After the stirring is completed, the temperature is lowered to room temperature to obtain an optical resin monomer product.

[0078] Example 5

[0079] An optical resin monomer, wherein the weight proportions of the components are:

[0080] 30 parts of dimethyl terephthalate, 60 parts of propylene alcohol, 38 parts of propylene glycol, 23 parts of methyltriethoxysilane, 7 parts of diethylene glycol, 4.5 parts of dibutyl maleate, 18.5 parts of nano-functional filler, 14.5 parts of polydimethylsiloxane, 1.85 parts of calcium hydroxide, 0.8 parts of TDL-ND1, and 4 parts of polyethylene glycol monoacrylate.

[0081] The present invention also discloses a method for preparing an optical resin monomer, comprising the following steps:

[0082] S1. Add 30 parts of dimethyl terephthalate, 60 parts of propylene alcohol and 0.9 parts of silicotungsto-molybdic acid-doped polyaniline catalyst into the reactor A by weight, start the stirring device, raise the temperature in the reactor to 120°C by programmed temperature rising method, and react at the set temperature;

[0083] S2, after the reaction is carried out for 20 hours, sampling is performed every 0.5 hours to detect the content of dimethyl terephthalate in the reaction system. When the content is less than 0.5%, stirring and heating are stopped to obtain a crude product of dipropylene terephthalate;

[0084] S3, refining the obtained crude dipropylene terephthalate;

[0085] S4, add the refined dipropylene terephthalate and 38 parts of propylene glycol into the reactor B, start the stirring device, raise the temperature in the reactor to 130° C. by the programmed temperature method, and react at the set temperature;

[0086] S5. After the reaction was carried out for 7.5 hours, the temperature in the kettle was lowered to 105°C, and 23 parts of methyltriethoxysilane, 14.5 parts of polydimethylsiloxane and 0.45 parts of platinum catalyst were added to the reaction system of reactor B and stirred for 2 hours;

[0087] S6. After stirring, add 18.5 parts of nano-functional fillers (nano-silicon dioxide, nano-titanium dioxide, nano-zinc oxide in a weight ratio of 6:7:5) and 0.8 parts of TDL-ND1 into the reactor B, and continue stirring for 1 hour;

[0088] S7, after the stirring is completed, the temperature in the kettle is lowered to 78.5°C, 4.5 parts of dibutyl maleate, 7 parts of diethylene glycol, 1.85 parts of calcium hydroxide, and 4.5 parts of polyethylene glycol monoacrylate are added to the reaction kettle B, and stirred for 1.5 hours;

[0089] S8. After the stirring is completed, the temperature is lowered to room temperature to obtain an optical resin monomer product.

[0090] The final products in Examples 1-5 were analyzed respectively, and Table 1 was plotted:

[0091]

[0092] Among them, the colorimetry adopts the platinum-cobalt colorimetry method, the moisture is analyzed by a moisture meter, the refractive index is analyzed by a refractometer, the acid value is determined by the acid-base titration method, and the kinematic viscosity is determined by a viscosity meter.

[0093] Take the prepared optical resin monomer, add dibenzyl phosphite and a photocuring agent (ESACURE ONE) to mix and stir to obtain a prepolymerization product, the mass ratio of the optical resin monomer to ESACURE ONE is 38:1, and the mass ratio of the optical resin monomer to dibenzyl phosphite is 42:1. Inject the prepolymerization product into a glass mold, and perform ultraviolet curing under ultraviolet light to obtain a resin lens.

[0094] The resin lenses prepared in Examples 1-5 were subjected to finished product inspection: according to GB / T2410-2008, the transmittance was tested using a UV-visible spectrophotometer; steel wool was placed on the surface of the resin lens, a load (5N) was applied to the steel wool, and rubbed 40 times back and forth, the surface was visually observed, and the wear resistance of the film layer was judged according to the number of scratches (0-5 scratches were excellent, 5-10 scratches were good, and more than 10 scratches were poor). The finished product inspection results are shown in the following table:

[0095]

[0096] According to the embodiments of the present invention as described above, these embodiments do not describe all the details in detail, nor do they limit the invention to specific embodiments. Obviously, many modifications and changes can be made based on the above description. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can make good use of the present invention and the modified use based on the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An optical resin monomer, characterized in that: The optical resin monomer is prepared from the following raw materials in parts by mass: 20-35 parts of dimethyl terephthalate, 50-65 parts of propylene alcohol, 30-40 parts of propylene glycol, 15-25 parts of methyltriethoxysilane, 5-8 parts of diethylene glycol, 3-5 parts of dibutyl maleate, 15-20 parts of nano-functional filler, 8-15 parts of polydimethylsiloxane, 0.5-2 parts of calcium hydroxide, 0.3-1 parts of dispersant, 1-5 parts of permeability enhancer; The nano functional filler is compounded by nano silicon dioxide, nano titanium dioxide and nano zinc oxide in a weight ratio of (2-5):(3-4):(2-3).

2. The method for preparing an optical resin monomer according to claim 1, characterized in that: The steps include: S1. Add 20-35 parts of dimethyl terephthalate, 50-65 parts of propenol and 0.5-1 part of catalyst A to reactor A by weight, start the stirring device, raise the temperature in the reactor to 115-125°C by programmed temperature rising method, and react at the set temperature; S2, after the reaction is carried out for 20 to 22 hours, sampling is performed every 0.5 hours to detect the content of dimethyl terephthalate in the reaction system. When the content is less than 0.5%, stirring and heating are stopped to obtain a crude product of dipropylene terephthalate; S3, refining the obtained crude product of dipropylene terephthalate; S4, add 30-40 parts of refined dipropylene terephthalate and propylene glycol to the reactor B, start the stirring device, raise the temperature in the reactor to 125-145° C. by a programmed temperature method, and react at the set temperature; S5. After the reaction is carried out for 7 to 8 hours, the temperature in the kettle is lowered to 105 to 115°C, 15 to 25 parts of methyltriethoxysilane, 8 to 15 parts of polydimethylsiloxane, and 0.2 to 0.5 parts of catalyst B are added to the reaction system of reactor B and stirred for 1 to 3 hours; S6. After the stirring is completed, add 15-20 parts of nano-functional filler and 0.3-1 parts of dispersant into the reactor B, and continue stirring for 0.5-1.5 hours; S7. After the stirring is completed, the temperature in the kettle is lowered to 75-85°C, 3-5 parts of dibutyl maleate, 5-8 parts of diethylene glycol, 0.5-2 parts of calcium hydroxide, and 1-5 parts of a permeability enhancer are added to the reaction kettle B, and stirred for 1-2 hours; S8. After the stirring is completed, the temperature is lowered to room temperature to obtain an optical resin monomer product.

3. The method for preparing an optical resin monomer according to claim 2, characterized in that: The refining treatment of the crude dipropylene terephthalate comprises the following steps: S31, after stopping stirring and heating, the crude product of dipropylene terephthalate is discharged from the reactor A for filtering; S32, the filtered crude dipropylene terephthalate is sent to a distillation tower for distillation to obtain refined dipropylene terephthalate.

4. The method for preparing an optical resin monomer according to claim 2, characterized in that: The catalyst A is a silicotungsto-molybdic acid-doped polyaniline catalyst.

5. The method for preparing an optical resin monomer according to claim 2, characterized in that: The catalyst B is a platinum catalyst.

6. The method for preparing an optical resin monomer according to claim 2, characterized in that: The permeability enhancer is polyethylene glycol monoacrylate.

Citation Information

Patent Citations

  • Optical resin monomer material and preparation method thereof

    CN101319024A

  • High-scratch-resistance optical resin monomer and preparation method thereof

    CN103172826A

  • Preparation method of optical resin monomer and reaction system thereof

    CN113831441A

  • Nano ceramic modified polyester resin and preparation method thereof

    CN114426762A

  • Resin monomer applicable to wear-resistant lens with refractive index of 1.56 and preparation method of resin monomer

    CN115286746A